Analysis of the Application of Fixed Asset Accounting in Consumer Cooperatives Sumber Rejeki Cakru - Rahmawati, Intan Nur; Susbiyani, Arik; Nuha, Gardina Aulin (West Science Accounting and Finance, 2025)
The analysis of the application of fixed asset accounting at the Sumber Rejeki Cakru Consumer Cooperative aims to provide an in-depth overview of its compliance with the Financial Accounting Standards Statement (PSAK) No. 16 of 2021. This study adopts a qualitative approach, employing data collection methods such as interviews, observations, and documentation. Based on the analysis of the recognition, measurement, depreciation, presentation, and disclosure of fixed assets, the cooperative has demonstrated compliance with the provisions of PSAK No. 16 of 2021. Fixed asset recognition is conducted by considering future economic benefits, the reliability of acquisition cost measurement, and the asset's intended purpose. In terms of measurement, the cooperative records the acquisition cost by including all relevant components until the asset is ready for use, covering non-monetary transactions and asset revaluation, if necessary. This practice reflects the cooperative's adherence to the applicable accounting standards in the implementation of fixed asset accounting